Metal Phosphorous Trichalcogenides (MPCh3 ): From Synthesis to Contemporary Energy Challenges - Gusmão, Rui; Sofer, Zdenek; Pumera, Martin (Angewandte Chemie (International ed. in English), 2019)
Owing to their unique physical and chemical properties, layered two-dimensional (2D) materials have been established as the most significant topic in materials science for the current decade. This includes layers comprising mono-element (graphene, phosphorene), di-element (metal dichalcogenides), and even multi-element. A distinctive class of 2D layered materials is the metal phosphorous trichalcogenides (MPCh3 , Ch=S, Se), first synthesized in the late 1800s. Having an unusual intercalation behavior, MPCh3 were intensively studied in the 1970s for their magnetic properties and as secondary electrodes in lithium batteries, but fell from scrutiny until very recently, being 2D nanomaterials. Based on their synthesis and most significant properties, the present surge of reports related to water-splitting catalysis and energy storage are discussed in detail. This Minireview is intended as a baseline for the anticipated new wave of researchers who aim to explore these 2D layered materials for their electrochemical energy applications.
Keywords: metal phosphorus trichalcogenides; energy storage; water splitting; 2D layered materials; batteries